Patriarchal System in Arabic Grammar - Ribut Nur Huda (Unisia, 2021)
The aim of this research is to find out the extent of the relationship between Arabic grammar and the patriarchal system in the Arab and Islamic society, which is represented in the well-known rule; Masculinity is more honorable than femininity. And the analysis of this relationship is his process under the approach of the philosophy of language, where he sees language as a living being with a linguistic context and a socio-cultural context. The researcher used the analytical and historical description method, taking advantage of the Sapper-Worf hypothesis (each language has a special grammatical structure), and from the theory of the companion Omar Ibn Al-Khattab (that the Arabic language is part of religion). After the depth of the analysis, the research concluded that the pattern of thought for grammatical predominance is like the constituent mind, with evidence that the nature of language is lightness in pronunciation or sound. As for the pattern of thought of the patriarchal system, it is like the made-up mind with evidence that the concepts of the text from the Qur’an and the Sunnah are affected by natural grammatical or abstract linguistic thinking. This research confirmed that the role of grammatical predominance in the patriarchal system is reflected in the level of Arabic-Islamic language and culture, and also that reflection appears in the level of belief and Sharia prominently. It is recommended that the subsequent researchers examine another topic of philosophical value in the same linguistic and cultural context, in order to understand the extent of external consistency in the relationship between the two contexts.